Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12889-019-7799-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of occupational injuries among building construction workers in Kampala City, Uganda

Abstract: BackgroundGlobally, about 1000 people die and close to 860,000 people sustain injury at work daily. Injury prevention and control require contextual evidence, although most studies in Uganda have focused on general causes. Factors associated with occupational injuries among building construction workers were assessed in this study.MethodsA cross-sectional study among building construction workers was conducted in Kampala, Uganda. A standardized semi-structured questionnaire was used to collect data. Three hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
14
1
1
Order By: Relevance
“…In the present study, the most common body parts injured were the upper extremities, with the hand being the most frequent location of the injury, in accordance with numerous studies describing the upper extremities as the most commonly affected body part [ 57 , 58 ]. Unlike previous evidence indicating lower extremities as the second-most-frequently injured body part [ 51 , 59 ], the results of the present study indicate that it is rather the head, followed by the lower extremities. This finding is concerning, given that a pooled proportions meta-analysis demonstrated that 17.9% of traumatic brain injuries are work-associated and 6.3% of occupational events result in traumatic brain injury (TBI) with 3.6% of work-related TBI being fatal [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the most common body parts injured were the upper extremities, with the hand being the most frequent location of the injury, in accordance with numerous studies describing the upper extremities as the most commonly affected body part [ 57 , 58 ]. Unlike previous evidence indicating lower extremities as the second-most-frequently injured body part [ 51 , 59 ], the results of the present study indicate that it is rather the head, followed by the lower extremities. This finding is concerning, given that a pooled proportions meta-analysis demonstrated that 17.9% of traumatic brain injuries are work-associated and 6.3% of occupational events result in traumatic brain injury (TBI) with 3.6% of work-related TBI being fatal [ 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The cross-sectional survey of construction workers found that the injuries with high incidence were mostly cuts and night-shift injuries. Therefore, strengthening education, publicity, and training, guaranteeing their rights to safety and protection at work, as well as legislative implementation, can help to reduce the occurrence of occupational injuries (26). The grass-roots construction workers need reasonable and effective training methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have found that job stress is related to higher odds of occupational accidents among building construction workers and coal miners [19,20].…”
Section: Introductionmentioning
confidence: 99%